ANALISIS RASIO PROFITABILITAS DAN RASIO AKTIVITAS SEBAGAI DASAR PENILAIAN KINERJA KEUANGAN PADA CV. MBF - Fauzi, Fauzi (EKONOMIKA, 2022)
The purpose of this research is to assess the financial performance of CV. MBF during the period 2019-2021, focuses on profitability ratios, activity ratios and performance evaluation compared to industry benchmarks. The research method used is qualitative, with the financial reports of CV. MBF serves as the main subject of analysis. Secondary data was used for this study, and data collection techniques included interviews and literature studies. The findings reveal that CV. MBF performed exceptionally well in terms of gross profit margin, exceeding the industry standard with an average of 61%. In addition, the net profit margin is also impressive, exceeding the industry average by 37%. Return on investment is considered satisfactory, standing at an average of 25% and meeting industry standards. However, when viewed from the activity ratio, CV. MBF has not managed its assets effectively. The average receivables turnover is much lower than the industry standard, only 5 times. Likewise, inventory turnover was below industry expectations at 1 time. On the other hand, total asset turnover is considered sufficient, with an average of 1 time, very much in line with industry standards. In conclusion, profitability ratios and activity ratios offer invaluable insights into a company's financial performance, resource utilization, cost control measures, and sales effectiveness and efficiency.